A taxonomic review of the Tracheliodes quinquenotatus (Jurine, 1807) species complex and some new records of rare European Tracheliodes A. Morawitz, 1866 (Hymenoptera, Crabronidae) - Divelec, Romain Le (Zootaxa, 2022)
Tracheliodes quinquenotatus (Jurine, 1807), as currently interpreted, is a widely distributed circummediterranean species. Three species are actually confused under this name. Two species are resurrected from synonymy: Tracheliodes trochantericus (Herrich-Schaeffer, 1841) stat. rev. and Tracheliodes herinaceus (Gribodo, 1894) stat. rev. One new synonymy is established: Crossocerus festivus Marquet, 1881 = Tracheliodes trochantericus (Herrich-Schaeffer, 1841) syn. nov. Neotypes are designated for Crossocerus luteicollis Lepeletier & Brullé, 1834 and Ceratocolus (?) trochantericus (Herrich-Schaeffer, 1841). Lectotypes are designated for Crossocerus festivus Marquet, 1881 and for Fertonius formicarius Ferton, 1896. New records for Tracheliodes curvitarsus (Herrich-Schaeffer, 1841) and Tracheliodes varus (Panzer, 1799) are provided.